Eimeria tenella protein trafficking: differential regulation of secretion versus surface tethering during the life cycle - V. Marugan-Hernandez (Nature Portfolio, 2017)
Abstract Eimeria spp. are intracellular parasites that have a major impact on poultry. Effective live vaccines are available and the development of reverse genetic technologies has raised the prospect of using Eimeria spp. as recombinant vectors to express additional immunoprotective antigens. To study the ability of Eimeria to secrete foreign antigens or display them on the surface of the sporozoite, transiently transfected populations of E. tenella expressing the fluorescent protein mCherry, linked to endogenous signal peptide (SP) and glycophosphatidylinositol-anchor (GPI) sequences, were examined. The SP from microneme protein EtMIC2 (SP2) allowed efficient trafficking of mCherry to cytoplasmic vesicles and following the C-terminal addition of a GPI-anchor (from surface antigen EtSAG1) mCherry was expressed on the sporozoite surface. In stable transgenic populations, mCherry fused to SP2 was secreted into the sporocyst cavity of the oocysts and after excystation, secretion was detected in culture supernatants but not into the parasitophorous vacuole after invasion. When the GPI was incorporated, mCherry was observed on the sporozites surface and in the supernatant of invading sporozoites. The proven secretion and surface exposure of mCherry suggests that antigen fusions with SP2 and GPI of EtSAG1 may be promising candidates to examine induction of protective immunity against heterologous pathogens.